Network-Centric Control: Concept and Essence ("Journal "U". Economy. Management. Finance.", 2018)
Nowadays much attention is paid to researches of different management systems, first of all, it is due to the need of timely adaptation to the changing factors of an external environment that leads to the improvement of the quality of structures’ functioning. Despite a large number of researches on this perspective, the universal and effective principle of control which could affect the capacity of the organization, as well as application of information and communication technologies, has not been revealed yet. The objective of this research consists in deep understanding of the network-centric control and determination of the need of its application within different structures.
Keywords: network-centric principle; network-centric management system; information and communication technologies; information system; information; network-centric approach; group control; model of an organization